Real-time changes in brain activity during sacral neuromodulation for overactive bladder: evidence from functional near-infrared spectroscopy - Luo, Runtian; Liao, Limin (Frontiers in Neuroscience, 2025)
ObjectiveThe mechanisms underlying overactive bladder (OAB) and the role of sacral neuromodulation (SNM) in its treatment are not fully understood. In this study, functional near-infrared spectroscopy (fNIRS) was used to identify changes in brain activity during SNM in patients with OAB who responded to therapy.MethodsWe employed a prospective trial method and idiopathic OAB patients selected for SNM treatment at our center were assigned to the experimental group and healthy adults matched by gender and age constituted the healthy control (HC) group. All participants completed 72-h urination diaries, the Overactive Bladder Symptom Score (OABSS), functional near-infrared spectroscopy (fNIRS) scans in both resting and task states, along with synchronous urodynamic monitoring. OAB patients were re-evaluated for these indicators after the SNM electrode implantation phase I test. The MATLAB toolbox NIRS-KIT was used to analyze and compare the differences in the internal functional connectivity (FC) of the prefrontal cortex (PFC) between the OAB group and the HC group before and after the treatment, in addition to assessing the differences in the PFC cortical activation/inactivation regions of the brain.Results1. A total of 10 HCs and 12 patients with OAB were included. After the SNM Phase I test, 10 patients with OAB were successful, while 2 patients failed. The average frequency of 24-h urination, the levels of urgency and incontinence, and OABSS in the OAB group were significantly higher than those in the HC group. After the SNM treatment, the parameters recorded in urination diaries, OABSS, and urodynamic measures in the successful OAB group were significantly improved compared to their levels before treatment. 2. Task fNIRS results: Compared to the HC group, BA9 (left dorsolateral prefrontal lobe) was significantly inactivated in the successful OAB group before SNM treatment. Compared to the HC group, there was no significant difference in brain activation after SNM treatment in the successful OAB group. BA9 (left dorsolateral prefrontal lobe) and BA45 (the triangular part of the left inferior frontal gyrus) were significantly activated after the SNM treatment in the successful OAB group in contrast to their activation levels before treatment. 3. Resting fNIRS results: Compared to the HC group, the FC of the PFC in the successful OAB group was significantly weakened in both the empty and filled bladder states before SNM treatment; however, after SNM treatment, it returned to normal. Compared to the HC group, there was no significant difference in the FC of OAB patients in the empty bladder state after treatment, but the FC was significantly activated during the strong desire to void state.ConclusionWe found abnormal deactivation of the FC in the PFC and left dorsolateral prefrontal lobe (BA9), which might lead to socially inappropriate involuntary urination and could be a central pathogenesis of OAB. SNM restored the functional connectivity in the left dorsolateral frontal lobe, the triangular part of the left inferior frontal gyrus, and the interior of the prefrontal lobe in patients with OAB, which may be one of the central mechanisms of SNM treatment for OAB. Our results may provide valuable insights into the central pathogenesis of OAB and the central mechanism of SNM treatment.